Molecular cloning and functional characterization of a two highly stereoselective borneol dehydrogenases from Salvia officinalis L. (April 2020) - Drienovská, Ivana; Kolanović, Dajana; Chánique, Andrea; Sieber, Volker; Hofer, Michael; Kourist, Robert
Abstract: Enzymes for selective terpene functionalization are of particular importance for industrial applications. Pure enantiomers of borneol and isoborneol are fragrant constituents of several essential oils and find frequent application in cosmetics and therapy. Racemic borneol can be easily obtained from racemic camphor, which in turn is readily available from industrial side-streams. Enantioselective biocatalysts for the selective conversion of borneol and isoborneol stereoisomers would be therefore highly desirable for their catalytic separation under mild reaction conditions. Although several borneol dehydrogenases from plants and bacteria have been reported, none show sufficient stereoselectivity. Despite Croteau et al. describing sage leaves to specifically oxidize one borneol enantiomer in the late 70s, no specific enzymes have been characterized. We expected that one or several alcohol dehydrogenases encoded in the recently elucidated genome of Salvia officinalis L. would, therefore, be stereoselective. This study thus reports the recombinant expression in E. coli and characterization of two enantiospecific enzymes from the Salvia officinalis L. genome, SoBDH1 and SoBDH2, and their comparison to other known ADHs. Both enzymes produce preferentially (+)-camphor from racemic borneol, but (−)-camphor from racemic isoborneol. Graphical abstract: Image 1 Highlights: Two novel borneol dehydrogenases identified in the genome of Salvia sp. Both enzymes show absolute selectivity towards (+)-borneol. Both enzymes produce preferentially (+)-camphor from racemic borneol, but (−)-camphor from racemic isoborneol. First examples of recombinantly produced selective borneol dehydrogenases. Potentially useful in the preparation of pure bioactive terpenoids, such as (−)-borneol and (−)-isoborneol.